The Mechanism of Ferroptosis and Applications in Tumor Treatment - Lin, Xinyue; Ping, Jieyi; Wen, Yi; Wu, Yan (Frontiers in Pharmacology, 2020)
Iron-dependent ferroptosis is a new form of cell death in recent years, which is driven by lipid peroxidation. The lethal lipid accumulation caused by glutathione depletion or inactivation of glutathione peroxidase 4 (GPX4) is characteristic of the ferroptosis process. In recent years, with the in-depth study of ferroptosis, various types of diseases have been reported to be related to ferroptosis. In other words, ferroptosis, which has attracted widespread attention in the fields of biochemistry, oncology, and especially materials science, can undoubtedly provide a new way for patients. This review introduces the relevant mechanisms of ferroptosis, the relationship between ferroptosis and various cancers, as well as the application of ferroptosis in tumor treatment. We also sorted out the genes and drugs that regulate ferroptosis. Moreover, small molecule compound-induced ferroptosis has a strong inhibitory effect on tumor growth in a drug-resistant environment, which can enhance the sensitivity of chemotherapeutic drugs, suggesting that ferroptosis is very important in the treatment of tumor drug resistance, but the details are still unclear. How to use ferroptosis to fight cancer, and how to prevent drug-resistant tumor cells have become the focus and direction of research. At the end of the article, some existing problems related to ferroptosis are summarized for future research.